2023
DOI: 10.3389/fnut.2023.1081263
|View full text |Cite
|
Sign up to set email alerts
|

A rose flavor compound activating the NRF2 pathway in dendritic cells ameliorates contact hypersensitivity in mice

Abstract: Dendritic cells (DCs), which are typical antigen-presenting cells, localize to various sites in the body, particularly the front line of infection as sentinels, and are involved in innate and adaptive immune responses. Although the functions of DCs, such as pathogen-induced cytokine production and antigen-specific T cell activation, are important for host defenses against infection and tumorigenesis, the hyper- and/or extended activation of DCs leads to inflammatory and autoimmune diseases. In the present stud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Previous studies reported that KetoC induced the expression of the antioxidant-related genes through the activation of NRF2, in the hepatic cell line HepG2 ( 18 ), and epithelial cell line Epi4 ( 9 ). In addition, a NRF2 deficiency enhanced the expression of IL-12p40 in stimulated DCs ( 14 , 19 ). Therefore, to confirm whether γKetoC induced an antioxidant response via the activation of NRF2 in DCs, we examined NRF2 protein levels in γKetoC-treated DCs using Western blotting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that KetoC induced the expression of the antioxidant-related genes through the activation of NRF2, in the hepatic cell line HepG2 ( 18 ), and epithelial cell line Epi4 ( 9 ). In addition, a NRF2 deficiency enhanced the expression of IL-12p40 in stimulated DCs ( 14 , 19 ). Therefore, to confirm whether γKetoC induced an antioxidant response via the activation of NRF2 in DCs, we examined NRF2 protein levels in γKetoC-treated DCs using Western blotting.…”
Section: Resultsmentioning
confidence: 99%
“…The extraction of total RNA, synthesis of cDNA, and quantitative PCR were performed as previously described ( 13 , 14 ). The nucleotide sequences of the primer sets used for qPCR are listed in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Mice were maintained under specific pathogen-free-conditions. BMDCs were generated by cultivating BM cells supplemented with recombinant mouse GM-CSF (#576308, BioLegend) or recombinant mouse Flt3L (550706, BioLegend) as previously described 15,27,31 . The cLNs were incubated in 100 μL of RPMI-1640 containing 10 mM HEPES (pH 7.4), 50 μg/mL Liberase TL, and 200 μg/mL DNaseI for 20 min at 37 ℃ with shaking to obtain a single-cell suspension.…”
Section: Methodsmentioning
confidence: 99%
“…The extraction of total RNA, synthesis of cDNA, and quantitative PCR were performed as previously described (13, 14). The nucleotide sequences of the primer sets used for qPCR are listed in Table I.…”
Section: Methodsmentioning
confidence: 99%